2016
DOI: 10.1113/jp270213
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on amyotrophic lateral sclerosis: the role of glial cells at the neuromuscular junction

Abstract: Amyotrophic lateral sclerosis (ALS) is a disease leading to the death of motor neurons (MNs). It is also recognized as a non-cell autonomous disease where glial cells in the CNS are involved in its pathogenesis and progression. However, although denervation of neuromuscular junctions (NMJs) represents an early and major event in ALS, the importance of glial cells at this synapse receives little attention. An interesting possibility is that altered relationships between glial cells and MNs in the spinal cord in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 103 publications
(277 reference statements)
6
65
0
Order By: Relevance
“…Because Schwann cell dissociation from NMJ is mainly caused by the axon retraction from motor plates (17,68), our results further suggest the halt of distal motor axon degeneration following treatment with masitinib. A potential important finding for ALS pathogenesis is the almost complete disappearance we found of capillaries in EDL muscle areas devoid of NMJ innervation.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Because Schwann cell dissociation from NMJ is mainly caused by the axon retraction from motor plates (17,68), our results further suggest the halt of distal motor axon degeneration following treatment with masitinib. A potential important finding for ALS pathogenesis is the almost complete disappearance we found of capillaries in EDL muscle areas devoid of NMJ innervation.…”
Section: Discussionsupporting
confidence: 57%
“…Perisynaptic Schwann cells are glial cells at the NMJs that ensure the synapse stability, maintenance, and repair during damage or denervation (41). Perisynaptic Schwann cells respond to ALS-induced denervation with profound morphological and phenotypic changes (17), retracting processes from the NMJs while extending processes to other endplate areas (42). Therefore, we examined whether downregulation of mast cells in masitinib-treated rats was associated to preservation of perisynaptic Schwann cells in the EDL muscle, as analyzed by confocal microscopy followed by 3-D reconstructions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Arbour et al . ). For example, in the context of muscle‐specific retrograde signalling to the neuromuscular junction, recent studies have shown that muscle‐specific disturbances in (1) autophagy (Carnio et al .…”
Section: Discussionmentioning
confidence: 97%
“…The neuromuscular junction is the interface between the motor neuron and muscle fibre and is a point of vulnerability in various neuromuscular diseases (Comley et al 2016;Boido & Vercelli, 2016) and normal ageing (Hepple & Rice, 2016). Importantly, previous studies have established that factors intrinsic to motor neurons, perisynaptic Schwann cells and muscle fibres may each contribute to neuromuscular junction degeneration in different contexts (Lieberman et al 2014;Sakellariou et al 2014;Arbour et al 2017). For example, in the context of muscle-specific retrograde signalling to the neuromuscular junction, recent studies have shown that muscle-specific disturbances in (1) autophagy (Carnio et al 2014), (2) the G93A mutation of superoxide dismutase 1 (SOD1) seen in a familial form of ALS (Dobrowolny et al 2018) and (3) FGFBP1 secretion (Taetzsch et al 2017) can each cause neuromuscular junction degeneration.…”
Section: Mechanisms Of Denervation and Reinnervation In Skeletal Musclementioning
confidence: 99%